Elucidation of the core betalain biosynthesis pathway in Amaranthus tricolor - Yu-Cheng Chang (Nature Portfolio, 2021)
Abstract Amaranthus tricolor L., a vegetable Amaranthus species, is an economically important crop containing large amounts of betalains. Betalains are natural antioxidants and can be classified into betacyanins and betaxanthins, with red and yellow colors, respectively. A. tricolor cultivars with varying betalain contents, leading to striking red to green coloration, have been commercially produced. However, the molecular differences underlying betalain biosynthesis in various cultivars of A. tricolor remain largely unknown. In this study, A. tricolor cultivars with different colors were chosen for comparative transcriptome analysis. The elevated expression of AmCYP76AD1 in a red-leaf cultivar of A. tricolor was proposed to play a key role in producing red betalain pigments. The functions of AmCYP76AD1, AmDODAα1, AmDODAα2, and AmcDOPA5GT were also characterized through the heterologous engineering of betalain pigments in Nicotiana benthamiana. Moreover, high and low L-DOPA 4,5-dioxygenase activities of AmDODAα1 and AmDODAα2, respectively, were confirmed through in vitro enzymatic assays. Thus, comparative transcriptome analysis combined with functional and enzymatic studies allowed the construction of a core betalain biosynthesis pathway of A. tricolor. These results not only provide novel insights into betalain biosynthesis and evolution in A. tricolor but also provide a basal framework for examining genes related to betalain biosynthesis among different species of Amaranthaceae.